CALCULATIONS OF PERFOMANCE PRODUCTIVITY OF ATC AS A QUEUING SYSTEM WITH FAILURES - I. N. Shestakov; M. I. Shestakova (Научный вестник МГТУ ГА, 2016)
The article give reasons for possibility of the investigation of the ATC system as a queuing system with failures. The concept of the failure is explained through the extreme condition of an ATC Unit. Criteria of the system’s performance productivity within the theory of queuing are given. The results of the calculations of the system’s productivity are provided.